2008
DOI: 10.1093/jac/dkn413
|View full text |Cite
|
Sign up to set email alerts
|

Has the licensing of respiratory quinolones for adults and the 7-valent pneumococcal conjugate vaccine (PCV-7) for children had herd effects with respect to antimicrobial non-susceptibility in invasive Streptococcus pneumoniae?

Abstract: This ecological analysis suggests that PCV-7 vaccination in children had a herd effect in adults, but consumption of respiratory quinolones in adults had no effect on pneumococcal susceptibility to levofloxacin in children. Penicillin/erythromycin non-susceptibility decreased along the studied period among paediatric invasive S. pneumoniae isolates to a level similar to that seen in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 14 publications
5
32
0
Order By: Relevance
“…The decline in the prevalence of resistance of S. pneumoniae to penicillin and, to a lesser degree, to erythromycin is in accordance with other reports (14,16,17,38). Several factors could have influenced the decrease in the prevalence of nonsusceptibility and resistance to penicillin observed in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decline in the prevalence of resistance of S. pneumoniae to penicillin and, to a lesser degree, to erythromycin is in accordance with other reports (14,16,17,38). Several factors could have influenced the decrease in the prevalence of nonsusceptibility and resistance to penicillin observed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Following the widespread use of the new conjugated heptavalent pneumococcal vaccine (PCV-7), a decrease in antibiotic resistance in pediatric pneumococcal isolates causing disease has been reported in several countries (5,38), not only in vaccinated individuals but also in unvaccinated individuals, as a result of the herd immunity effect (16). Nevertheless, some recent studies have observed an increase in the prevalence of drug-resistant S. pneumoniae as a result of an increase in the prevalence of the more resistant nonvaccine serotypes (27).…”
mentioning
confidence: 99%
“…Yearly serotype distribution among pleural isolates showed a significant decreasing trend for PCV-7 serotypes in the total population (R 2 ϭ 0.829; ␤ ϭ Ϫ0.919; P Ͻ 0.001) ( Table 1), adults (R 2 ϭ 0.701; ␤ ϭ Ϫ0.853; P Ͻ 0.001) ( Table 2), and children (R 2 ϭ 0.330; ␤ ϭ Ϫ0.625; P ϭ 0.030) ( Table 3), as occurred in a previous study by our group analyzing all invasive isolates received by the SRLP (associated with an increase in PCV-7 distribution) (8).…”
supporting
confidence: 65%
“…Tables 1 to 3 show yearly distribution of invasive and pleural isolates (with their susceptibilities) for the total population, adults, and children, respectively. In the current decade, the number of S. pneumoniae invasive isolates received by the SRLP has increased, reflecting the increase in the number of voluntarily participating Spanish hospitals due to the increasing interest in post-PCV-7 licensure surveillances (8).…”
mentioning
confidence: 99%
“…After the introduction of the 7-valent pneumococcal conjugate vaccine (PCV7) into childhood vaccination calendars, rates of IPD caused by the seven serotypes covered by the vaccine (4, 6B, 9V, 14, 18C, 19F, and 23F) have decreased substantially not only among vaccinated children but also among unvaccinated children and adults as a result of the reduced nasopharyngeal carriage of pneumococcus in vaccinated children and the reduced transmission to unvaccinated populations (3,5). In addition, an increase in the incidence of IPD caused by non-PCV7 serotypes has been observed (4,21) with an increase in penicillin nonsusceptibility (9,10), mainly due to serotype 19A (11,18,20). Postlicensure monitoring of IPD is important to track potential changes in the IPD disease burden caused by nonvaccine serotypes, since IPD varies widely depending on such factors as geographical area, age, race, and site of infection (16).…”
mentioning
confidence: 99%